Application of fever triage system in emergency pre-examination and triage of COVID-19 patients (发热患者分诊系统在新型冠状病毒肺炎急诊预检分诊中的应用效果) - CHEN Xi (陈曦) (中西医结合护理)
Objective To evaluate the application of febrile patient triage system in emergency pre-examination and triage of COVID-19 patients. Methods In this study, 132 febrile patients treated at hospital from March 2019 to March 2022 were selected for a retrospective study. Patients were divided into two groups: 66 patients in the control group received routine triage management, while another 66 patients in the study group were managed by using a fever triage system. The triage management was evaluated and compared between two groups. Results Ten patients were triaged to receiving high-risk management in the fever clinic, and one suspected COVID-19 case was detected. After screening, there was no confirmed COVID-19 case, missed diagnosis or nosocomial infection occurred, and the diagnostic accuracy was 100. 00%. The study group had a less time spent on triage time higher patient satisfaction than those in the control group, with a significant difference (P<0. 05). Conclusion The application of fever triage system in emergency pre-examination triage of COVID-19 patients can effectively improve the efficiency of triage, enhance the effectiveness of COVID-19 and nosocomial infection prevention, as well as patient satisfaction. (目的 分析发热患者分诊系统在新型冠状病毒肺炎急诊预检分诊中的应用效果。方法 回顾性分析2019年3月—2022年3月医院接诊的132例发热患者的资料, 按照分诊方式分为两组。其中, 未采取发热患者分诊系统进行急症预检分诊的66例患者为对照组, 采取发热患者分诊系统进行急症预检分诊的66例患者为研究组, 分析和对比应用效果。结果 10例患者经分诊至发热门诊高危区域, 检出新型冠状病毒肺炎疑似病例1例, 筛查后无确诊病例, 未发生漏诊及院内感染情况, 诊断准确率100. 00%。与对照组相比, 研究组分诊用时更短、患者满意度更高, 差异有统计学意义(P＜0. 05)。结论 在新型冠状病毒肺炎急诊预检分诊中应用发热患者分诊系统, 能有效提升分诊效率, 提高院内感染风险防范效果, 提升患者满意度。)